Beyond Carbon, More Than Forest? REDD+ Governmentality in Indonesia. (January 2015) - McGregor, Andrew; Challies, Edward; Howson, Peter; Astuti, Rini; Dixon, Rowan; Haalboom, Bethany; Gavin, Michael; Tacconi, Luca; Afiff, Suraya
Reducing Emissions from Deforestation and forest Degradation (REDD+) is an expanding global initiative oriented at slowing or reversing carbon emissions from forests in the Global South. The programme is based on the principle of payment for environmental services, where the carbon sequestration services of forests are seen to have a financial value which can be paid for through grant and market mechanisms. In this paper we explore how REDD+ is implemented, drawing upon the concept of governmentality. We focus on REDD+ practices in Indonesia, concluding with a case study focused on the Sungai Lamandau REDD+ project in Central Kalimantan. A cross-scalar approach is adopted that explores the different but overlapping strategies of actors congregating at international, national, and local scales. We detail the neoliberal strategies employed by international actors; the more disciplinary approaches evident within national planning processes; and local forms of engagement being practised by a forest community. Our findings reveal REDD+ to be comprised of a heterogeneous regime of disjointed practices that reflect the existing political ecologies and interests of differently located actors. Rather than consolidate these approaches we argue that the strength of the programme lies in its fluidity, which is creating new cross-scalar opportunities, and risks, for those pursuing forms of social and environmental justice.